The legal concept of artificial intelligence: the debate surrounding the definition of AI System in the AI Act (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The concept of AI has always been controversial because there is no broad consensus on its definition. This is problematic from a legal perspective, as laws require precise and specific definitions, especially for concepts that have a direct impact on the scope and reach of the regulation, having this choice technological, economical and legal implications. During the European Union’s AI Act legislative process, there has been a debate on the legal definition of AI, with diverging definitions of AI System being proposed by the different bodies of the European Union.
Keywords: Artificial Intelligence; legal definitions; AI Act; legislative process; European Union institutions